2020
DOI: 10.5051/jpis.1905320266
|View full text |Cite
|
Sign up to set email alerts
|

Angled implant brush for hygienic maintenance of full-arch fixed-implant rehabilitations: a pilot study

Abstract: Purpose This pilot study was conducted to evaluate the cleaning efficacy of an angled implant brush for home oral hygiene of full-arch fixed-implant prostheses. Methods Forty-one patients treated with a full-arch implant rehabilitation in the maxilla or mandible (164 implants) for at least 4 months were enrolled. The screw-retained fixed prostheses were removed and baseline (T0) parameters were recorded, including plaque index (PI), probing depth (PD), and bleeding on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Meanwhile, it has been reported that patients who have been totally edentulous or with a terminal dentition for a long time are often unable to cooperate with oral hygiene maintenance at home. [17][18][19][20][21] Therefore,improving the oral cleanliness and reducing plaque accumulation are feasible measures to prevent biological complications for patients with full-arch implant-supported fixed prostheses. However, patients with full-arch implant-supported fixed prostheses have reported difficulties in cleaning the prostheses and maintaining oral hygiene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Meanwhile, it has been reported that patients who have been totally edentulous or with a terminal dentition for a long time are often unable to cooperate with oral hygiene maintenance at home. [17][18][19][20][21] Therefore,improving the oral cleanliness and reducing plaque accumulation are feasible measures to prevent biological complications for patients with full-arch implant-supported fixed prostheses. However, patients with full-arch implant-supported fixed prostheses have reported difficulties in cleaning the prostheses and maintaining oral hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that poor oral hygiene and plaque accumulation are major risk indicators for peri‐implant disease, including peri‐implant mucositis, which is characterized by the presence of peri‐implant signs of inflammation, and peri‐implantitis, the clinical manifestations of which also include peri‐implant bone loss 1–16 . Meanwhile, it has been reported that patients who have been totally edentulous or with a terminal dentition for a long time are often unable to cooperate with oral hygiene maintenance at home 17–21 . Therefore,improving the oral cleanliness and reducing plaque accumulation are feasible measures to prevent biological complications for patients with full‐arch implant‐supported fixed prostheses.…”
Section: Introductionmentioning
confidence: 99%